Geographical distribution, abundance and some population characteristics of the species of the genus Pagellus (Osteichthyes: Percirformes) in different areas of the Mediterranean - Maria Teresa Spedicato; Silvestro Greco; Kostas Sophronidis; Giuseppe Lembo; Daniela Giordano; Anna Argyri (Scientia Marina, 2002)
The objective of this paper was to investigate the local distribution, abundance and population structure of Pagellus erythrinus, Pagellus bogaraveo and Pagellus acarne on the continental shelf and slope over a wide geographic area from Gibraltar to the Aegean Sea. The analysis was based on the data collected during six trawl surveys, from 1994 to 1999, carried out yearly in spring within the MEDITS EU project. P. acarne was mainly distributed on the continental shelf, with a relatively higher abundance in the western part of the Mediterranean basin, where the biomass indices of P. bogaraveo were also important on the continental slope. Throughout the studied area, P. erythrinus was mainly distributed on the continental shelf, with remarkable abundance indices in the eastern part of the Mediterranean and in Corsica´s waters. Mean total lengths showed a highly significant decreasing trend from the western to the eastern geographical sectors.